ANALISIS RASIO KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR FOOD AND BERVERAGE (STUDI KASUS PADA PT. AKASHA WIRA INTERNASIONAL, TBK) - Al Faruk Islamudin; Aris Munandar; Wulandari (Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to determine and analyze financial ratios against share prices in Food and Divergence Sub-Sector Companies This research used an associative research method. The research instrument used was a list of tables consisting of the variable indicators Current Ratio, Debt To Equity Ratio, Return On Assets, Total Asset Turnover and PT share price. Akasha Wira Internasional, Tbk for 10 years, namely from 2013 to 2022. The population in this research is the financial statements of PT. Akasha Wira Internasional, Tbk has been listed on the IDX from 1994 to 2022, which is 28 years. The sample in this research is the financial report of PT. Akasha Wira Internasional, Tbk for 10 years, namely from 2013 to 2022. The sampling technique used in this research was purposive sampling. data was collected by documentation and literature study. Data analysis carried out to answer the hypothesis used the t test and f test. The research results show that Current Ratio (CR), Debt To Equity Ratio (DER), Return On Assets (ROA) and Total Asset Turnover (TATO) have a significant effect on share prices at PT. Akasha Wira Internasional, Tbk.